A Rare Case of HPV-Negative Cervical Squamous Cell Carcinoma. (March 2015) - Casey, Shauna; Harley, Ian; Jamison, Jackie; Molijn, Anco; van den Munckhof, Henk; McCluggage, W. Glenn
Abstract : It is generally assumed that virtually all cervical squamous cell carcinomas are associated with persistent infection by high-risk human papillomavirus (HPV), although it is well known that unusual variants of cervical adenocarcinoma are mostly HPV negative. We report a case of a well-differentiated cervical squamous cell carcinoma in a 54-yr-old woman, the morphologic features of which suggested a non-HPV-related neoplasm. The tumor was p16 negative. HPV was also negative by 2 methods, including the highly sensitive SPF-10 system. Further study of additional cases is needed to establish the etiological and pathogenetic factors that underlie very rare non-HPV-related cervical squamous cell carcinoma.